The life of Robert Stephenson, F.R.S. etc. etc., late President of the Institution of Civil Engineers : with descriptive chapters on some of his most important professional works by William Pole, F.R.S., member of the Institution of Civil Engineers. Vol. II - Jeaffreson, John Cordy, 1831-1901 (Longman, Green, Longman, Roberts & Green, 1864)
This second volume of biography covers: the battle of railway gauges; Stephenson's work on iron bridges; the Britannia bridge; the high-level bridge at Newcastle; his work on the Chester and Holyhead Railway; his political career; his time in London society; the Victoria bridge in Canada; his final years.
Includes index.
Keywords: Stephenson, Robert, -- 1803-1859.; Railroad engineers -- Great Britain -- Biography.; elektronické knihy; electronic books